Analysis of Monoraphidium griffithii’s Polyunsaturated Fatty Acids: Implications for Biodiesel Properties and Anticancer Potential - Vinitha Vivekanandan; Meignanalakshmi Sundaram (Scientific Research, New Technologies and Applications Vol. 4, 2024)
Background: The rich biochemical and physiological properties of microalgae are considered to be valuable sources of commercial importance. Microalgae are able to synthesize a wide range of biomolecules, including biologically active metabolites that have significant potential in a wide range of commercial applications, due to their distinct morphological, physiological, and genetic features. Aim: The aim of the study was to isolate and characterize freshwater microalgae to analyze its biochemical composition including protein, carbohydrate, pigments, lipid, poly-unsaturated fatty acid content, anticancer activity, cytotoxicity, and biodiesel properties. Methodology: Pure isolate obtained from freshwater was characterized biochemically and identified by ITS-2 RNA sequence as Monoraphidium griffithii. The microalgal culture was grown in media containing macronutrients (MgSO4, KH2PO4, K2HPO4, CaCl2, NaCl, NaNO3) and micronutrients (Iron stock, Boron stock, EDTA, Zn, Co) and maintained under white light illumination for a photoperiod of 16:8 light/dark hours respectively. The saturated and poly-unsaturated fatty acid profiling was performed in a Gas Chromatography-Flame ionization detector and the biodiesel properties were analyzed through BiodieselAnalyzer© Ver. 2.2 software. Results: The biochemical composition was determined to be 32.97%±1.648 protein, 15.36%±2.857 carbohydrate, 15.89%±1.407 lipid, 26.27±1.48 µg/mg chlorophyll a+b and 8.03±1.92 µg/mg carotenoid. The fatty acid profiling revealed the presence of 19 different fatty acids of which Palmitic acid was 18.08%, cis-10 heptadecanoic acid was 17.37%, alpha-linolenic acid was 2.05%, and docosahexaenoic was 1.27%. The fatty acid profile showed that the isolated freshwater microalgae have good biodiesel properties as per ASTM standards and better cold flow properties. 46.5% cell viability was attained at a microalgal concentration of 80 µg/ml against the human lung cancer cell line (A549) and the cell viability was 77.87% even at the high concentration of 100 µg/ml against the Vero cell line. Conclusion: The presence of alpha-linolenic and docosahexaenoic acid and anticancer activity makes them a source of human and animal nutrition. The isolated strain also has anticancer activity and it is non-toxic to normal cells. Therefore, the isolated strain was found to have the potential to be used for biodiesel production and also to be used as a food and feed additive.